The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1007/s00404-017-4345-5
|View full text |Cite
|
Sign up to set email alerts
|

The influence of the systematic birth preparation program on childbirth satisfaction

Abstract: Systematic birth preparation program improves satisfaction with childbirth experience by enabling women to communicate better with healthcare providers and to participate in decision-making during labor, as well as by decreasing the perception of labor pain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
5

Year Published

2018
2018
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 21 publications
1
31
1
5
Order By: Relevance
“…These findings are not surprising, as antenatal education and good companionship have been reported to improve women’s satisfaction by helping them have realistic expectations of the experience and teaching them to maintain control during labor. [33,34] However, in the present study, only 27.1% of the participants attended prenatal health education sessions. Regarding the presence of companionship, approximately 90% of the participants reported that they had someone (most commonly their husband) present during the first stage of labor.…”
Section: Discussioncontrasting
confidence: 64%
“…These findings are not surprising, as antenatal education and good companionship have been reported to improve women’s satisfaction by helping them have realistic expectations of the experience and teaching them to maintain control during labor. [33,34] However, in the present study, only 27.1% of the participants attended prenatal health education sessions. Regarding the presence of companionship, approximately 90% of the participants reported that they had someone (most commonly their husband) present during the first stage of labor.…”
Section: Discussioncontrasting
confidence: 64%
“…Health education delivered through childbirth education (CBE) and preconception/ interconception (P/I) education are critical components of comprehensive reproductive health programming. CBE has positive outcomes for labor including reducing fear, anxiety, and the perception of pain as well as increasing selfefficacy, decision-making, communication with providers and perceived support and control (Akca et al, 2017;Isbir, Inci, Onal, & Yildiz, 2016). Given the unique needs and experiences of women in drug treatment, childbirth education could be especially important.…”
Section: Childbirth Education (Cbe) and Preconception/interconception (P/i) Educationmentioning
confidence: 99%
“…La preparación prenatal intensiva y multidisciplinaria ha demostrado en Turquía una elevada satisfacción de las puérperas pues se redujo el nivel del dolor y mejoró la comunicación durante el parto, independientemente del nivel sociocultural de las gestantes (37) . El servicio de triage al ingreso al Servicio de Obstetricia también favorece la satisfacción de las usuarias (38) .…”
Section: Del Nacionalunclassified